2013
DOI: 10.1111/echo.12489
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Blood Pressure Recovery Ratio and Its Relation to Endothelial Function and Left Ventricular Diastolic Function in Prediabetics

Abstract: Abnormal HRR1 and delayed SBP response detected during recovery imply a significant correlation with impaired endothelial function and diastolic dysfunction in prediabetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The systematic search resulted in the inclusion of 193 from a total of 4641 potential articles (Figure ). From the 193 studies included in the analyses, vascular reactivity was assessed in a total of 26570 patients that were considered healthy (n = 7226), overweight (n = 7605), or those with obesity (n = 1758) or that were diagnosed with metabolic sy...…”
Section: Resultsmentioning
confidence: 99%
“…The systematic search resulted in the inclusion of 193 from a total of 4641 potential articles (Figure ). From the 193 studies included in the analyses, vascular reactivity was assessed in a total of 26570 patients that were considered healthy (n = 7226), overweight (n = 7605), or those with obesity (n = 1758) or that were diagnosed with metabolic sy...…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, HRR was negatively correlated with post-exercise systolic and diastolic BP and was positively correlated with systolic and diastolic BPR, and these associations are consistent with the underlying understanding that after exercise sympathetic withdrawal and parasympathetic reactivation dramatically decrease HR and BP (Cole et al, 1999; Laborde et al, 2018; Laukkanen et al, 2004; Tanindi et al, 2015). This dynamic flux in sympathetic and parasympathetic activity is responsible for a number of hemodynamic changes including a drop in total peripheral resistance and cardiac output (Gourine & Ackland, 2019; Laukkanen et al, 2004; Mahfouz et al, 2014; Tanindi et al, 2015). Given that the sympathetic nervous system directly innervates vessel walls, this may partially explain the association between HRR and hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the sympathetic nervous system directly innervates vessel walls, this may partially explain the association between HRR and hemodynamics. Mahfouz et al (2014) reported abnormal HRR and poor systolic BPR were significantly correlated with impaired endothelial function and diastolic dysfunction among a sample of prediabetic patients (Mahfouz et al, 2014). Also, given the cohort of professional firefighters was largely hypertensive and overweight, it is reasonable to assume there may have undiagnosed cardiometabolic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahfouz et al . [ 19 ], suggested that abnormal HRR and delayed systolic blood pressure recovery after exercise were correlated with impaired endothelial function and diastolic dysfunction in prediabetics.…”
Section: Introductionmentioning
confidence: 99%